The State-Centric Approach to Preventing Political Violence: An International Framework - Nevil D’Cunha (Eurasian Journal of Management & Social Sciences)
This article takes the declared goal of preventing violent political conflicts as a starting point. Today, the whole world is starving for peace: from Somalia to Syria, from Sierra Leone to Libya, political violence is the plague of our age. At the outset, the concept of violence itself needs to be considered. The general view is that violence entails the use of physical force, usually with the purpose of injuring or damaging the target of the violence. In the political world, the weapons of such violence can range from gunshots, flying fists, and nuclear missiles to chemical agents. The central actor in violent political conflicts is usually the ‘state.’ Prevention entails attempting everything to enable nations to avert the outbreak of emergencies that take a high toll on humanity, undermining institutions, and capacities to achieve development and peace. In order to continually achieve this task, robust mechanisms to prevent future conflict risks needs to be put in place. In an interdependent world, this means that for preventing political violent conflicts there is a dire need for an international architecture that works across countries and refocused on prevention rather than containment. This paper proposes to do a thematic analysis of the joint United Nations and World Bank Report on preventing violent conflict in the light of political violence expounded by Danziger. This thematic analysis can enable us to understand both the anatomy of political violence and the international architecture to prevent their future occurrence. This study can make a significant contribution to address the immense challenges facing collective humanity’s contemporary quest for peace.